2020
DOI: 10.3390/foods9081070
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Supplementation of a Diet Low in Calcium and Phosphorus with Either Sheep Milk or Cow Milk on the Physical and Mechanical Characteristics of Bone using A Rat Model

Abstract: This study assessed the effect of cow milk (CM) and sheep milk (SM) consumption on the micro-structure, mechanical function, and mineral composition of rat femora in a male weanling rat model. Male weanling rats were fed a basal diet with a 50% reduction in calcium and phosphorus content (low Ca/P-diet) supplemented with either SM or CM. Rats were fed for 28 days, after which the femora were harvested and stored. The femora were analyzed by μ-CT, three-point bending, and inductively coupled plasma–mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Milk provides calcium and phosphorus in a reasonable ratio of 1.3:1. Burrow et al (2020) reported that animal experiments have shown a significant increase in trabecular bone volume and BMD in rats when cow's milk is supplemented with a calcium-phosphorus-deficient diet (50% reduction in calcium and phosphorus). This suggests that milk may help to counteract the negative effects of insufficient calcium-phosphorus intake on bone health.…”
Section: Malmir Et Al (2020)mentioning
confidence: 99%
“…Milk provides calcium and phosphorus in a reasonable ratio of 1.3:1. Burrow et al (2020) reported that animal experiments have shown a significant increase in trabecular bone volume and BMD in rats when cow's milk is supplemented with a calcium-phosphorus-deficient diet (50% reduction in calcium and phosphorus). This suggests that milk may help to counteract the negative effects of insufficient calcium-phosphorus intake on bone health.…”
Section: Malmir Et Al (2020)mentioning
confidence: 99%
“…The consumption of sheep milk by rats fed a diet restricted in calcium and phosphorous contents was found to increase the levels of calcium, phosphorous, and strontium in the bones of the rats, and thereby it has a good prospect of maintaining bone health in diets low calcium and phosphorous [17].…”
Section: Health Benefitsmentioning
confidence: 99%